1997
DOI: 10.1080/00224549709595427
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Color Preferences and Body Satisfaction Among South Asian-Canadian and European-Canadian Female University Students

Abstract: Skin-color preferences and body satisfaction among 100 South Asian-Canadian and 100 European-Canadian female university students were examined. South Asian-Canadian females were found to desire lighter skin than they possessed and had lower body satisfaction compared with European-Canadian females. Among South Asian-Canadians, the desire to be lighter skinned was greater the more participants differed from the cultural White ideal. Light- and medium-skinned South Asian-Canadians had the highest and lowest leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 25 publications
2
72
0
Order By: Relevance
“…The results revealed that the Asians in Hong Kong were actually more dissatisfied with their body and weight than the Asians in the United States. Thus, although previous research has shown that Asian females in traditionally Western countries such as United States and Canada tend to be particularly dissatisfied with racially defined features, such as their eyes, face and skin colour (Forbes & Frederick, 2008;Koff, Benavage, & Wong, 2001;Mintz & Kashubeck, 1999;Sahay & Piran, 1997), as it seems, levels of body dissatisfaction may be even higher among Asians in Hong Kong. People in Hong Kong have in fact also shown their higher vulnerability to experiencing body dissatisfaction in comparison with people in less westernized parts of China, such as Hunan and Shenzhen (Lee & Lee, 2000).…”
Section: Cultural Differences In Body Dissatisfactionmentioning
confidence: 65%
See 1 more Smart Citation
“…The results revealed that the Asians in Hong Kong were actually more dissatisfied with their body and weight than the Asians in the United States. Thus, although previous research has shown that Asian females in traditionally Western countries such as United States and Canada tend to be particularly dissatisfied with racially defined features, such as their eyes, face and skin colour (Forbes & Frederick, 2008;Koff, Benavage, & Wong, 2001;Mintz & Kashubeck, 1999;Sahay & Piran, 1997), as it seems, levels of body dissatisfaction may be even higher among Asians in Hong Kong. People in Hong Kong have in fact also shown their higher vulnerability to experiencing body dissatisfaction in comparison with people in less westernized parts of China, such as Hunan and Shenzhen (Lee & Lee, 2000).…”
Section: Cultural Differences In Body Dissatisfactionmentioning
confidence: 65%
“…In comparisons between different ethnic groups within Western countries it has been demonstrated that dissatisfaction with aspects that are not related to one's body size appears, nonetheless, to be important dimensions of Black and Asian women's body dissatisfaction. For instance, being light-skinned is idealized among both Black and Asian women (Altabe, 1998) and Asian women tend to be more dissatisfied than White women with their height, breasts, eyes and face (Forbes & Frederick, 2008;Koff et al, 2001;Mintz & Kashubeck, 1999;Sahay & Piran, 1997). We know little about whether these results may generalize to females in non-Western countries, but the high prevalence of women in Korea that undergo plastic surgery to change their racially defined features into looking more 'Western' (Kawamura, 2002) is an indication that this may be the case.…”
Section: Measurementsmentioning
confidence: 99%
“…5 Some researchers stated that people evaluated the performance of image based on the reference of subjective expectations and ideal colors. 7 Nevertheless, these researchers illustrated the complex process that affected people's color recognition and the numerous factors that influenced people's preferences. [8][9][10] Many psychological factors have been proved to be influential to the preferences of image colors, taking familiarity with color for example, Bodrogi and Tarczali 11 pointed out that people's preferences with image colors showed significant differences depending on the images.…”
Section: Studies Of Color Preferencementioning
confidence: 98%
“…The complexities of colorism and its effects vary between and within ethnic groups. Research has revealed the role that colorism plays in social status, upward mobility, employment status, marital status, criminal sentencing, politics, acculturation, relationship desirability, psychological health, and self-esteem in black, Latino, and Asian communities (Brown, Ward, Lightbourn, & Jackson, 1999;Gomez, 2000;McDonald, 2006;Philips, 2004;Sahay, 1997).…”
mentioning
confidence: 97%
“…Burgos also noted how most professional Latino players participated in the Negro Leagues and were subjected to the same mistreatment as black baseball players, and their contributions were often overlooked by the mainstream and black press. In other parts of the world, it is believed that European colonialism, slavery practices, and the era of Western empires, during which people of color internalized notions of "White superiority," led to the adoption of Caucasian beauty ideals that placed lightness at the top and darkness at the bottom (Hunter, 2002;Sahay, 1997). Mass communication via television, print, and the Internet, as well as the cosmetic industry, continue to play a significant role in reinforcing the effects of colorism (Adebajo, 2002;Glenn, 2008;Keenan, 1996).…”
mentioning
confidence: 99%